Dynamics of the Emergence of Donor Trust in Online Fundraising Organizers - Aryndi, Azalia Elfreda; Muhammad, Amri Hana (Universitas Negeri Semarang, 2023)
Fundraising is a social activity based on the encouragement the desire to help each other to those in need. Increasingly advanced technology, fundraising is now carried out online so that potential donors can reach them easily. Online fundraising means that users can only interact virtually with fundraising organizers without having to meet in person, so the trust that arises from donors is important until a decision is made to donate. The dynamics of the emergence of trust is important to generate trust in online fundraising organizers. This research was conducted using a qualitative research method with a descriptive exploratory research design. The data sources in this study were five informants who were donors from online fundraising. This study uses semi-structured interviews. Data analysis techniques in this study used inductive thematic analysis techniques. The validity of the data uses a member check. The results of the study show that prospective donors start from the experience of giving previous donations and are encouraged by moral values and then aim to provide online donation assistance which will see transparency of the platform and description of fundraising information provided by the organizer through information regarding donation targets, documentary evidence, and track record of the organizer which then raises an assessment that will result in the emergence of trust in the organizer.